Evaluation of the presence of lateral canals in lower molars by means of computed tomography: longitudinal study in a new software - Diaz Espinoza, German (2022)
In the present study, CBCT from the database of the Bauru Dental School was used. High resolution tomographic images of patients treated in the period between (2014 to 2019) were selected. For the evaluation of the images a computer equipped with a processor Intel Core 2 Duo-6300 with 1.86 GHz, an NVIDIA GeForce 6200 cache turbo graphics card and an EIZO-Flex scan S2000 monitor with a resolution of 1600 x 1200 pixels and Windows XP SP-2 professional was used. The sample number was 200 teeth divided into 2 groups for analysis: G1: 100 (e-Vol DX software, CDT software, Bauru, SP, Brazil) and G2: 100 (3D software Accuitomo 170 J. Morita, Kyoto, Japan) and for scanning the images, 1024 views were performed following the pattern: 3D, thickness of 0.100 mm, dimensions of 1.170 x 1.570 x 1.925 mm, field of view of 56.00 mm, voxel size of 0.100 mm and exposure time 33.5 seconds, the tube voltage will be 90 kVp and the tube current will be 4 mA. For the analysis of data regarding the location of the lateral canal in the mesial buccal root MBR in the cervical, middle and apical thirds for both the G1 software e-Vol DX and the G2 software 3D Accuitomo 170, the fisher exact test was used and for the location of the canal. lateral in the mesial lingual root LRM, and in the root DR in the cervical, middle, apical thirds were evaluated by chi-square test. In G1, it was possible to detect and locate the lateral canal with greater precision in the MBR in the cervical third (30.11%), in the LRM in the middle third (46.99%), and in the DR in the apical third (23.53%). In G2, the location of the lateral canal in the MBR was in the cervical third (3.45%), in the LRM in the middle third (10.20%), and in the DR in the apical third (13.64%). Using the e-Vol DX, it was analyzed that the distance from the MR of the LM1 in relation to the mandibular canal was 5.14 mm (standard deviation of 1.99), while from the DR to the mandibular canal it was 4.41 mm (standard deviation of 1.99). default of 1.98). As for the LM2, the MR showed an average distance of 3.32 mm in relation to the mandibular canal (standard deviation of 1.71 mm) and an average distance of 2.99 mm of the DR in relation to the mandibular canal (standard deviation of 1 .75 mm). In conclusion, the e-Vol DX software (Software CDT, Bauru, SP, Brazil) was able to more accurately and efficiently locate the presence of the lateral canal in both MBR, LRM and DR. In addition to locating the distance that exists between the MR and DR of the first and second permanent lower molars in relation to the mandibular canal.